PENCAPAIAN AKTUALISASI TOKOH UTAMA DALAM NOVEL KATA KARYA RINTIK SEDU MELALUI PENDEKATAN PSIKOLOGI HUMANISTIK ABRAHAM MASLOW - Ayu, Alya Sekar; Damayanti, Aprina; J. Daulay, Muhammad Anggie (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to reveal how someone’s psychological state using the humanistic psychology approach of Abraham Maslow, the physiological needs, the safety needs, the belongingness and love needs, the esteem needs, and the needs for self-actualization. The data source of this research is a novel entitled “Kata” by Rintik Sedu published by Gagas Media. The focus of this research object is on humanistic psychology analysis, especially at the level of hierarchical needs. This research achievement comes from the novel “Kata” by Rintik Sedu using qualitative descriptive methods, with steps including reading and noting, data reduction, data categories, and corpus data. The results show that there are five levels or hierarchies of Abraham Maslow’s humanistic psychological needs that exist in the main character of “Kata” novel by Rintik Sedu.